La Variation Pragmatique Régionale en Français - Farenkia, Bernard Mulo (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2012)
This study describes and compares the realization of the speech act of complimenting in Cameroon and Canadian (Québec) French. It is a contribution to cross-cultural pragmatics in the francophonie, with focus on non-hexagonal varieties of French. Keywords: non-hexagonal French, speech acts, regional variation RÉSUMÉ Cette étude analyse et compare la formulation de l’acte de compliment en français camerounais et en français canadien (québécois). Elle contribue à la pragmatique contrastive et interculturelle des pratiques langagières en francophonie, avec un accent particulier sur les français dits périphériques. Mots-clés : français périphériques, actes de langage, variation diatopique